2016
DOI: 10.1089/gtmb.2015.0168
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Polymorphisms of DNA Repair Genes and Risk of Schizophrenia

Abstract: Our findings support XRCC1, XRCC3, hOGG1, and XPD as risk genes for schizophrenia and suggest that altered DNA repair functions may be involved in schizophrenia pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The over‐expression of 8‐oxoguanine DNA glycosylase (OGG1) is the hallmark of the normal brain aging (Lu et al, ). It is reported that the interaction between OGG1 and X‐ray repair cross complementing 1 has been implicated in schizophrenia (Derakhshandeh, Saadat, Farrashbandi, & Saadat, ; Odemis et al, ; Psimadas et al, ; Saadat, Pakyari, & Farrashbandi, ) and autism spectrum disorder (Shpyleva et al, ; Xu, Rosales‐Reynoso, Barros‐Nunez, & Peprah, ; Young, McKinney, Ross, Wahle, & Boyle, ). It is found that the expression of OGG1 is increased in white matter oligodendrocytes of patients with MDD (Szebeni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The over‐expression of 8‐oxoguanine DNA glycosylase (OGG1) is the hallmark of the normal brain aging (Lu et al, ). It is reported that the interaction between OGG1 and X‐ray repair cross complementing 1 has been implicated in schizophrenia (Derakhshandeh, Saadat, Farrashbandi, & Saadat, ; Odemis et al, ; Psimadas et al, ; Saadat, Pakyari, & Farrashbandi, ) and autism spectrum disorder (Shpyleva et al, ; Xu, Rosales‐Reynoso, Barros‐Nunez, & Peprah, ; Young, McKinney, Ross, Wahle, & Boyle, ). It is found that the expression of OGG1 is increased in white matter oligodendrocytes of patients with MDD (Szebeni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was reported that XRCC1 gene (Arg399Gln) variant Gln399Gln genotype was associated with Sch in South Indian population (47). Odemis et al (48) showed that XRCC1 (Gln) and XRCC3 (Thr) alleles were signifi cantly more frequent among the patients with Sch than the controls.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that biallelic mutations in human XRCC1 are associated with ocular motor apraxia, axonal neuropathy, and progressive cerebellar ataxia [24]. It has been reported that XRCC1 rs25487 Gln/Gln and Arg/Gln genotypes were more common in patients with schizophrenia than healthy controls [25,26]. However, Celik et al and Czarny et al showed that XRCC1 rs25487 variant had no significant association with obsessive-compulsive disorder (OCD) and recurrent depressive disorder [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…People with XPD 751Gln/Gln have been shown to manifest suboptimal DNA repair capacity to remove UV photoproducts when compared to the XPD 751Lys/Lys and Lys/Gln genotypes [8]. Odemis et al and Celik et al found that XPD Lys751Gln variant Lys/Lys genotype frequency was increased in patients with schizophrenia and in OCD comparison to controls [26,27]. In the present study, we showed that Gln/Gln genotype was higher in subjects with cannabis and/or synthetic cannabis dependence than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%